Participação do sistema endocanabinoidérgico no mecanismo antinociceptivo da ketamina - Renata Cristina Mendes Ferreira (2014)
The ability to feel pain is essential for maintenance of the life, without her tissue trauma would not be detected or prevented, causing significant tissue and nerve damage. The discovery of new analgesic mechanisms is the goal of several studies, such as researches related to ketamine, a drug discovered in the 60's and originally used as a dissociative general anesthetic that has recently come to be also used as an analgesic in chronic pain. The present study evaluated the involvement of endocannabinoids in the antinociceptive effect peripheral, spinal and supraspinal, induced by ketamine against the hyperalgesia evoked by prostaglandin E2 (PGE2) 2 µg/paw. The antinociceptive activity was evaluated using mechanical paw withdrawal rat test subjected to compression. Ketamine caused a dose-dependent antinociceptive effect in the peripheral (10, 20, 40 and 80 µg), intrathecal (20, 40 and 80 µg) and intracerebroventricular (1, 2, 4 and 8 µg), with peak action in five minutes. Measurements made in the contralateral paw showed that at a dose of 80 µg/paw, ketamine not alter the nociceptive threshold in the untreated paw in peripheral pathway. CB1 receptor antagonist (AM251) reversed dose-dependent the antinociceptive effect of ketamine in peripheral (20, 40 and 80 µg), spinal (20, 40 and 80 µg) and supraspinal (1, 2 and 4 µg) pathways. However, the CB2 receptor antagonist (AM630) reversed the antinociceptive effect only the supraspinal pathway of dose-dependent manner, demonstrating the involvement of CB1 receptors in the peripheral, spinal and supraspinal pathways, and this last route, involvement with the CB2 cannabinoid receptor type was also observed. The fatty acid amide hydrolase enzyme inhibitor, FAAH, (MAFP) (2, 4 and 0,2 µg) and the inhibitor of reuptake of anandamide (VDM11) (20, 20 and 4 µg) for peripheral, intrathecal and intracerebroventricular pathways respectively, responded synergistically with ketamine in the intermediate dose (20, 40 and 2 µg) in the antinociception for the respective routes. The MGL (monoacylglycerol lipase) enzyme inhibitor (JZL184) was used only in spinal (14 µg) and supraspinal (7 µg) pathways, and was able to enhance the analgesic effect of ketamine (40 and 2 µg), respectively. In addition to the behavioral experiments, was also studied the presence of the endocannabinoids anandamide (AEA), 2-araquidonoil glicerol (2-AG), palmitoiletanolamida (PEA) and oleiletanolamida (OEA), in the paw of rats after treatment with ketamine through the technique of gas chromatography and mass spectrometry. Was found an increase of AEA in paws treated with PGE2 + ketamine, but not the other endocannabinoids. The peripheral, spinal and supraspinal antinociceptive effect of ketamine is possibly related to alternative antinociceptive mechanisms not involving the NMDA receptor. It’s can mobilize the cannabinoid system in the different study pathways through the hypotheses: Binding directly in cannabinoid receptors; Direct release of endocannabinoids or even the release of endogenous opioid peptides which in turn, induce the release of endocannabinoids; and finally by mechanisms involving the activation of opioid-cannabinoid receptor complex. Thus, our study examined the involvement of the cannabinoid system in the peripheral, intrathecal and intracerebroventricular antinociception of ketamine. This study further strengthens the possibility of use of ketamine as an analgesic in clinical practice of pain control, as well as fostering the possibility of further studies that may elucidate how these systems interact in several analgesic pathways studied.